Identification of Antibiotic Dose Appropriateness in Patients with Non-Pneumonia Acute Respiratory Tract Infection at Community Health Center X - Ayu Putri MS; Handa Riyatul Masruroh; Shinta Mayasari; Wima Anggitasari (LPPM Universitas dr. Soebandi, 2026)
An Non-pneumonia acute respiratory tract infection (ARTI) is one of the most common diseases in the community and a frequent cause of patient visits to healthcare facilities. Based on a preliminary study, non-pneumonia ARTI was among the ten most prevalent diseases at Community Health Center X, with 266 reported cases during the period of January–December 2025. The high incidence of non-pneumonia ARTI has led to increased antibiotic use. Therefore, antibiotics should be used rationally, including through appropriate dosing. Inappropriate antibiotic dosing may reduce therapeutic effectiveness and increase the risk of bacterial resistance. This study aimed to identify the appropriateness of antibiotic dosing in patients with non-pneumonia ARTI at Community Health Center X. This study employed a descriptive observational design with a retrospective approach. A total of 160 patients were selected using purposive sampling. Data were collected from the medical records of patients with non-pneumonia ARTI, and the appropriateness of antibiotic dosing was evaluated based on the Community Health Center X Formulary. Data were analyzed using univariate analysis. The results showed that, among the 160 patients with non-pneumonia ARTI, the largest age group was children aged 0–5 years, accounting for 46 patients (28.8%). Amoxicillin was the most frequently prescribed antibiotic (77%), followed by ciprofloxacin (23%). The most commonly prescribed dosage strengths were amoxicillin 500 mg (48.1%), amoxicillin 125 mg (18.8%), and ciprofloxacin 500 mg (23.1%). The most common dosing frequency was three times daily (76.9%), followed by twice daily (23.1%). Evaluation of antibiotic dose appropriateness showed that all 160 patients (100%) received appropriate antibiotic doses. In conclusion, all patients with non-pneumonia ARTI at Community Health Center X received appropriate antibiotic doses.